Ukrainian Iconography of the Late XX–Early XXI Century: Trends and Leading Schools - Kovalchuk, Ihor M.; Stelmashchuk, Halyna H.; Patyk, Roksolana S.; Benyakh, Nataliya M.; Babunych, Yuliya I.; Honcharuk, Oleksandr V. (The journal of contemporary issues in business and government, 2021)
The article deals with the development of modern Ukrainian iconography, the formation of the main centers and regional schools, traces artistic and stylistic features and trends. The article analyzes the activities of the Kyiv and Lviv Art Schools in the field of sacred art. The main features of the development of modern iconography are identified, the creativity of leading specialists and iconographers, genres and technological specifics of iconography are studied. The scientific novelty of this research consists in a comprehensive study of modern Ukrainian iconography, taking into account artistic and stylistic, regional, technological, and canonical aspects. Features of formation of art schools and associations of sacred art in Ukraine are traced. The aim of the study is to determine the main trends in the development of modern Ukrainian iconography, to identify the influence of leading schools in the field of sacred art. The methodological basis is a comprehensive approach to the analysis of cultural and artistic phenomena in the chronological and theoretical aspects of the development of modern sacred art in Ukraine.